2018
DOI: 10.1177/0972150917749722
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the Technical Efficiency of Traditional and Corporate Agents in Indian Life Insurance Industry: Slack-based Data Envelopment Analysis Approach

Abstract: The distribution channels play an imperative role in the life insurance industry. In India, traditional and corporate agency are contributing immensely to the profitability of the insurance companies. The challenges faced by the distributional channels such as high attrition, soaring expense ratio and sales inefficiency have created the need to probe into the efficiency aspects of the channel players. In the absence of such studies in India, this article evaluates the technical efficiency of distribution chann… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 37 publications
0
5
0
Order By: Relevance
“…To the authors' best knowledge, there are 22 studies on the specific case of the Indian insurance sector. Among these 22 studies, Tone and Sahoo (2005), Sinha (2007aSinha ( , 2012Sinha ( , 2015, Sinha and Chatterjee (2009), Dutta and Sengupta (2011), Chakraborty et al (2013), Chakraborty (2016a), Parida and Acharya (2017), Anandarao et al (2018), Shetty and Basri (2018) and Savitha et al (2019) focussed on the life insurance sector. Sinha (2007bSinha ( , 2017a Mandal and Dastidar (2014), Bawa and Kaur (2014) and Chakraborty (2016bChakraborty ( , 2018 zeroed in on the nonlife insurance sector.…”
Section: Related Literaturementioning
confidence: 99%
See 1 more Smart Citation
“…To the authors' best knowledge, there are 22 studies on the specific case of the Indian insurance sector. Among these 22 studies, Tone and Sahoo (2005), Sinha (2007aSinha ( , 2012Sinha ( , 2015, Sinha and Chatterjee (2009), Dutta and Sengupta (2011), Chakraborty et al (2013), Chakraborty (2016a), Parida and Acharya (2017), Anandarao et al (2018), Shetty and Basri (2018) and Savitha et al (2019) focussed on the life insurance sector. Sinha (2007bSinha ( , 2017a Mandal and Dastidar (2014), Bawa and Kaur (2014) and Chakraborty (2016bChakraborty ( , 2018 zeroed in on the nonlife insurance sector.…”
Section: Related Literaturementioning
confidence: 99%
“…Besides, it found that the mean productivity growth of the private insurers is higher than the public insurers. Shetty and Basri (2018) utilised DEA to assess efficiency of traditional individual agents and corporate agents in the life insurance market. The study uses the panel data set of 12 life insurers for the period 2012-2016.…”
Section: Related Literaturementioning
confidence: 99%
“…Because millions of insurers, healthcare providers, patients, and consumers are involved in the insurance ecosystem (Shetty & Basri, 2017), it is easy for the industry to get hindered by money-and time-wasting inefficiencies resulting from billions of forms, human error and poor coordination between parties (Shetty & Basri, 2020).…”
Section: Fidentiaxmentioning
confidence: 99%
“…Anandarao et al (2019) reported that ICICI Prudential Life Insurance, Shriram Life Insurance and Tata AIA Life Insurance rank first in the overall efficiency along with LIC. Shetty and Basri (2020) divulged that there was no significant difference in the efficiency scores of traditional and corporate agents. Roy and Saha (2018) too observed that the LIC was the only efficient company.…”
Section: Review Of Literaturementioning
confidence: 99%